Pre-COVID-19 hospital quality and hospital response to COVID-19: examining associations between risk-adjusted mortality for patients hospitalised with COVID-19 and pre-COVID-19 hospital quality - Michelle Schreiber; Jing Zhang; Yongfei Wang; Zhenqiu Lin; Arjun K Venkatesh; Lee A Fleisher; Elizabeth W Triche; Lisa G Suter; Doris Peter; Shu-Xia Li; Jacqueline Grady; Kerry McDowell; et al. (BMJ Open, 2024)
Objectives The extent to which care quality influenced outcomes for patients hospitalised with COVID-19 is unknown. Our objective was to determine if prepandemic hospital quality is associated with mortality among Medicare patients hospitalised with COVID-19.Design This is a retrospective observational study. We calculated hospital-level risk-standardised in-hospital and 30-day mortality rates (risk-standardised mortality rates, RSMRs) for patients hospitalised with COVID-19, and correlation coefficients between RSMRs and pre-COVID-19 hospital quality, overall and stratified by hospital characteristics.Setting Short-term acute care hospitals and critical access hospitals in the USA.Participants Hospitalised Medicare beneficiaries (Fee-For-Service and Medicare Advantage) age 65 and older hospitalised with COVID-19, discharged between 1 April 2020 and 30 September 2021.Intervention/exposure Pre-COVID-19 hospital quality.Outcomes Risk-standardised COVID-19 in-hospital and 30-day mortality rates (RSMRs).Results In-hospital (n=4256) RSMRs for Medicare patients hospitalised with COVID-19 (April 2020–September 2021) ranged from 4.5% to 59.9% (median 18.2%; IQR 14.7%–23.7%); 30-day RSMRs ranged from 12.9% to 56.2% (IQR 24.6%–30.6%). COVID-19 RSMRs were negatively correlated with star rating summary scores (in-hospital correlation coefficient −0.41, p<0.0001; 30 days −0.38, p<0.0001). Correlations with in-hospital RSMRs were strongest for patient experience (−0.39, p<0.0001) and timely and effective care (−0.30, p<0.0001) group scores; 30-day RSMRs were strongest for patient experience (−0.34, p<0.0001) and mortality (−0.33, p<0.0001) groups. Patients admitted to 1-star hospitals had higher odds of mortality (in-hospital OR 1.87, 95% CI 1.83 to 1.91; 30-day OR 1.46, 95% CI 1.43 to 1.48) compared with 5-star hospitals. If all hospitals performed like an average 5-star hospital, we estimate 38 000 fewer COVID-19-related deaths would have occurred between April 2020 and September 2021.Conclusions Hospitals with better prepandemic quality may have care structures and processes that allowed for better care delivery and outcomes during the COVID-19 pandemic. Understanding the relationship between pre-COVID-19 hospital quality and COVID-19 outcomes will allow policy-makers and hospitals better prepare for future public health emergencies.